Regulation of Forest Police’ Authorities in Enforcing Illegal Logging Law in Mount Ciremai National Park - Yudhistira, Donny; Ramadhan, Mahendra Utama Cahya; Furqon, Eki; Akhmaddhian, Suwari; Hidayat, Sarip (Universitas Kuningan, 2024)
This study aims to understand the regulation of illegal logging in Indonesia as well as to analyse the implementation of forest police authorities in combating illegal logging in Mount Ciremai National Park. This study applied a juridical-empirical approach that involves literature study and field research in which the primary, secondary, and tertiary data were collected through observation and interviews. The results indicated that illegal logging is governed in Articles 12, 19, 82, 83, and 87 of Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction, and the forest police authorities are regulated in Article 51 paragraph (2) of Law No. 41 of 1999 on Forestry and Article 4 paragraph (2) of the Regulation of the Minister of Forestry of the Republic of Indonesia No. P.75/Menhut-II/2014 on Forest Police, which serve as the regulatory framework for forest police in addressing illegal logging in Mount Ciremai National Park. In carrying out his/her authorities, the forest police apply 3 (three) approaches, namely preemptive, preventive, and repressive. Hence, it can be concluded that illegal logging is governed by Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction, and the implementation of forest police authorities in combating illegal logging is carried out through a preemptive, preventive, and repressive approach. Finally, it is suggested that law enforcement officials must be consistent and firm in taking action against illegal logging to create a deterrent effect, and the improvement of facilities and infrastructure is urgently needed.